1997
DOI: 10.1093/rheumatology/36.8.870
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin is safe and superior to placebo in elderly-onset rheumatoid arthritis

Abstract: The efficacy, toxicity and possible steroid-sparing properties of auranofin in the treatment of elderly-onset rheumatoid arthritis (EORA) were studied in a 2 yr prospective double-blind placebo-controlled clinical trial. Sixty-five patients with onset of arthritis after the age of 60 yr were randomized to either auranofin 3 mg b.i.d. [n = 31, age 70 (61-84) yr, median (range)] or placebo tablets [n = 34, age 72 (60-81) yr]. Oral prednisolone, starting dose 7.5 or 20 mg daily, was used as a rescue drug in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…Other studies on the effectiveness of SAARDs were often of shorter duration, or included fewer patients. Summarising these studies, moderate effectiveness of hydroxychloroquine and auranofin has been reported,5 31while better effectiveness for other SAARDs has been found, without clear differences between these SAARDs 1132-34 As for radiological damage, patients treated with IM gold, methotrexate, or sulfasalazine had a slower progression than those treated with hydroxychloroquine, auranofin, or azathioprine when three different trials were compared 20…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on the effectiveness of SAARDs were often of shorter duration, or included fewer patients. Summarising these studies, moderate effectiveness of hydroxychloroquine and auranofin has been reported,5 31while better effectiveness for other SAARDs has been found, without clear differences between these SAARDs 1132-34 As for radiological damage, patients treated with IM gold, methotrexate, or sulfasalazine had a slower progression than those treated with hydroxychloroquine, auranofin, or azathioprine when three different trials were compared 20…”
Section: Discussionmentioning
confidence: 99%
“…Extensive clinical use of AF has shown that this drug has a relatively safe pharmacological profile in humans including elderly patients (Glennas et al, 1997;Kean et al, 1997;Kim et al, 2010). This, in combination with its anti-inflammatory and cytoprotective activity demonstrated by this study may make AF a good treatment option for inflammatory conditions other than rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 57%
“…Auranofin has a well‐defined toxicity profile and an acceptable safety for human use (Glennas et al ).Furthermore, studies have demonstrated that auranofin has antibacterial activity against methicillin‐resistant Staphylococcus aureus (MRSA) (Cassetta et al ; Hokai et al ) and inhibitory activity against Gram‐positive bacteria, enterococci, fungi and parasites (Andrade and Reed ; Roder and Thomson ). As such, auranofin has been studied not only as an anti‐rheumatic agent, but also as an antimicrobial agent.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to find a substance that could act as an anti-biofilm and antimicrobial agent among substances that are already approved for human use. Auranofin has a well-defined toxicity profile and an acceptable safety for human use (Glennas et al 1997). Furthermore, studies have demonstrated that auranofin has antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA) (Cassetta et al 2014;Hokai et al 2014) and inhibitory activity against Gram-positive bacteria, enterococci, fungi and parasites (Andrade and Reed 2015;Roder and Thomson 2015).…”
Section: Discussionmentioning
confidence: 99%